x-47=-39

Simple and best practice solution for x-47=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-47=-39 equation:


Simplifying
x + -47 = -39

Reorder the terms:
-47 + x = -39

Solving
-47 + x = -39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '47' to each side of the equation.
-47 + 47 + x = -39 + 47

Combine like terms: -47 + 47 = 0
0 + x = -39 + 47
x = -39 + 47

Combine like terms: -39 + 47 = 8
x = 8

Simplifying
x = 8

See similar equations:

| 78n+100=550 | | 3(x-3)+21=3x+12 | | -5m+4m+2=5m+8 | | 5(x-8)+9=-60 | | 8=-2p-10 | | 4(-8h-8)=-3h+200 | | 6x+21=4x-57 | | 3-4(x-2)-4=-3x-3-6 | | 41=7x-8 | | 6d+10=12d-5 | | -7k-4k=-4k-k-12 | | x+17=3x-3 | | t+30=22 | | (x-3)(x-3)-12=0 | | 5-3n=-6n-13 | | -9-2f=5f-23 | | 7c+3(c-4)=8 | | 111=-12x+15 | | 30-15w=2w-6 | | 2x+2+7=16 | | -2x+4=ax+b | | 6x-5=7x-13 | | 1+2x=-7+x | | 4(2x+1)=8x+11 | | 6x-6+x-3=2x-1 | | 3(2x-5)=81 | | 5x+87=54 | | -7n+8=15 | | 2x-10=2x+20 | | z-16=-15 | | 5z-2=4z | | 8n-32+8n=-128 |

Equations solver categories